Peripheral administration of a humanized anti-PrP antibody blocks Alzheimer's disease Aß synaptotoxicity - ROWAN, MICHAEL (My University, 2014)
Alzheimer's disease (AD) is associated with pathological assembly states of amyloid-β protein (Aβ). Aβ-related synaptotoxicity can be blocked by anti-prion protein (PrP) antibodies, potentially allowing therapeutic targeting of this aspect of AD neuropathogenesis. Here, we show that intravascular administration of a high-affinity humanized anti-PrP antibody to rats can prevent the plasticity-disrupting effects induced by exposure to soluble AD brain extract. These results provide an in vivo proof of principle for such a therapeutic strategy.
Keywords: Alzheimer's disease